Arginine anchor points govern H3 tail dynamics - Jennings, Christine E.; Zoss, Casey J.; Morrison, Emma A. (Frontiers in Molecular Biosciences, 2023)
Chromatin is dynamically reorganized spatially and temporally, and the post-translational modification of histones is a key component of this regulation. The basic subunit of chromatin is the nucleosome core particle, consisting of two copies each of the histones H2A, H2B, H3, and H4 around which ~147 base pairs of DNA wrap. The intrinsically disordered histone termini, or tails, protrude from the core and are heavily post-translationally modified. Previous studies have shown that the histone tails exist in dynamic ensembles of DNA-bound states within the nucleosome. Histone tail interactions with DNA are involved in nucleosome conformation and chromatin organization. Charge-modulating histone post-translational modifications (PTMs) are poised to perturb the dynamic interactions between histone tails and DNA. Arginine side chains form favorable interactions with DNA and are sites of charge-modulating PTMs such as citrullination. Our current focus is on the H3 tail, the longest histone tail. Four arginine residues are relatively evenly spaced along the H3 tail sequence, suggesting multivalent interactions with DNA poised for regulation by PTMs. In this study, we use NMR nuclear spin relaxation experiments to investigate the contribution of arginine residues to H3 tail dynamics within the nucleosome core particle. By neutralizing arginine via mutation to glutamine, we begin to work towards a comprehensive understanding of the contribution of individual residues to H3 tail dynamics. We find that neutralization of arginine residues results in increased regional mobility of the H3 tails, with implications for understanding the direct effects of arginine citrullination. Altogether, these studies support a role for dynamics within the histone language and emphasize the importance of charge-modulating histone PTMs in regulating chromatin dynamics, starting at the level of the basic subunit of chromatin.